Wrist Snap for Humanoid Robot Drumming - Cho, Jungsoo; Yim, Sehyuk (2023 20TH INTERNATIONAL CONFERENCE ON UBIQUITOUS ROBOTS, UR, 2023)
Drumming requires good wrist snap to play right. The wrist snap mechanism has been found that the wrist and stick tip differ in velocity at the point of hitting and apex timing at the end of lifting through the previous work. It has also been observed that drummers control acceleration differently than non-drummers. From this, the wrist snap mechanism is reconstructed and implemented into a humanoid robot.